DYNAMICS NOISE BEHAVIORS ON MAGNETO-OPTICAL KERR EFFECT MEASUREMENT SYSTEM - Handoko, Djati; Kim, Dong-Hyun (Indonesian Physical Review, 2023)
Nowadays, computer and data processing industry are moving to nanomagnetic devices technology. One of the common measurement systems to observe nanomagnetic device are magneto optical Kerr effect and Faraday effects. The magneto-optical Kerr effect measurement system has been fabricated and precision noise measurement configuration was observed. A light intensity, which was reflected by thin film nanomagnetic surface, was measured accompany with its noise level. The lock-in amplifier was attached to pick up hysteresis signal and low noise level. Different frequency of lock-in amplifier was carried out to observe dynamics noise level behavior. Interestingly, we found butterfly shape noise corresponding to hysteresis loop shape. Furthermore, Â noise behavior with 0.94 scaling exponent, was found with respect to lock-in amplifier frequencies suggested that measuring in low frequency became more challenging.